Security risk analysis of IaaS based on the abstract state machine model. (2016) - Shuang, Xiang; Bo, Zhao; Yu, Xiao; Yang, An
In order to handle the problem of a lack of formal modelling for the IaaS and its validation, this paper focuses on the interactions between internal components triggered by user behaviour, modelling the IaaS service as the interactions between the users and the entities within inter-cloud platform, as well as the entities within cloud platform. We take the abstract state machine (ASM) as operation semantics for formalising communication model when using IaaS platform services, which can show the changes of dynamic performance about the platform status. Meanwhile, we simplify the model without sacrificing the service correctness from user's perspective. Finally, we give the security attributes of cloud services and find some threats prone to service failure by using model checking tools UPPAAL to analyse the performance of current IaaS platform. This paper also provides a theory fundamental for the security enforcement of IaaS service and contributes to the prevailing of cloud computing.